TVET in Botswana : a case study on its ability to develop demand-driven and competence-based skills for the labour market - Koobonye, Sara [Verfasser] (Bundesinstitut für Berufsbildung, 2020)
"Botswana has turned out as an exemplary development success amongst other African countries. Despite its commendable development, there is still high youth unemployment rate. This master thesis examines Botswana's TVET system in terms of its ability to develop competence-based skills that are relevant for the needs and demands of the labour market. Due to the lack of research in Botswana, this case study had an exploratory character. The demand orientation on the needs of the labour market is organised by a sector committee that determines the developments and what kind of programmes will be required in the upcoming five years. One of the significant findings of this research is the correlation between political engagement and society's appreciation of TVET. Due to a neglection of TVET in political decision making, physical resources in schools are outdated and do not meet the standards of industry. As a consequence, students learn the techniques on old models. Compared to other countries, Botswanan TVET students are sometimes not competitive with other nations in Africa and globally. Therefore, it may be the perfect time for political authorities to invest in reforming the system. Several recommendations have been made. Most important factor is adequate funding of TVET. Self-employment as a means of job creation is highly encouraged and through various programmes supported. By these programmes, unemployed youth and early school-dropouts find access to further education and training." (Autorenreferat ; BIBB-Doku)
Keywords: S System beruflicher Bildung; S 2.3 Berufsbildungspolitik; G 1.2 Arbeitsmarkt; I 2.3.1 Afrika; Bildungssystem; Berufsbildungssystem; Berufsbildungspolitik; Bildungsfinanzierung; Kompetenzorientierung; Arbeitsmarkt; Botswana